Formulation des pâtes alimentaires enrichies avec germe de blé cas de Tlitli - ABBOU, Houria; BRAHIM, Naima (My University, 2023)
The aim of this study is to formulate an improved food dough with wheat germ. This formulation will be evaluated on several levels, technological suitability and feasibility, culinary improvements, sensory characteristics and consumer acceptability. By incorporating 3% wheat germ into the formula, we have found that the composition of the finished product is closer to the standards required for a commercial quality accessible to Algerian consumers. Enriching our formula with 3% wheat germ results in a 1.5-fold increase in protein content, a 1.78-fold decrease in lipid content and a 1.04-fold reduction in carbohydrate content. The results of the organoleptic quality test showed that Tlitli dough enriched with wheat germ had good color, a smooth appearance, good firmness, a pleasant characteristic taste, and a shorter cooking time than commercial Tlitli. Analysis of the production and cost costs of our trials shows maximized profit for production, marketing and the consumer. These results show that our product will be highly competitive on the market. Based on data collected through an online questionnaire, it appears that Algerian consumers are showing interest in the arrival on the market of a range of pasta products enriched with an organic product, a by-product of cereal processing, of marketable quality and at a reasonable price.
Keywords: Pasta; wheat germ; enrichment; nutritional value; protein; culinary quality; value-added